Monte Carlo dosimetric parameter study of a new (32)P brachytherapy source - Wu, Junxiang (Br J Radiol, 2016)
OBJECTIVE: Recently, a new catheter-based (32)P brachytherapy source has been developed (College of Chemistry, Sichuan University) for use in high-dose-rate afterloader. This study presents the results of the dosimetric data of the Geant4 Monte Carlo (MC) simulation toolkit for this new (32)P brachytherapy source. METHODS: The new (32)P source had dimensions of 0.50-cm length and 0.08-cm diameter and was encapsulated in teflon. In this study, we attempted to obtain dosimetric data for this new source, as required by the formalism proposed by the American Association of Physicists in Medicine reports TG60 and TG149. The source was located in a 30-cm radius theoretical sphere water phantom, and the absorbed dose of the source was calculated using MC code. RESULTS: The dosimetric data included the reference absorbed dose rate, the radial dose function in the range of 0.10–0.50 cm at a longitudinal axis, the polynomial function for the radial dose function and the anisotropy function with a θ value of 0–90° in 5° intervals and an r of 0.10–0.35 cm in 0.01-cm intervals. The radial and axial dose profiles and away-along quality assurance table are also calculated for the unsheathed (32)P source. The dose rate D(r(0),θ(0)) at the reference point for the unsheathed (32)P source is determined to be equal to 1.2660 ± 0.0006 cGy s(−1) mCi. The radial dose function of the new (32)P source shows good agreement with the other (32)P source presented in this work with an average difference of 1.78%. CONCLUSION: Dosimetric data are provided for the new (32)P source. These data could be used in treatment-planning systems in clinical practice. ADVANCES IN KNOWLEDGE: Provided a new beta-emitting brachytherapy source that is intended for treatment of liver cancer. A dosimetric study of the unsheathed (32)P source for which no published dosimetric data existed was performed.